Identity and lectotypification of Amomum compactum and Amomum kepulaga (Zingiberaceae). Issue 6 (25th October 2013) - Droop, Jane; Kaewsri, Wittaya; Lamxay, Vichith; Poulsen, Axel D.; Newman, Mark
Abstract: Amomum compactum Sol. ex Maton (Java cardamom) is widely cultivated across Southeast Asia as a spice and medicine. Confusion has surrounded this species both morphologically and nomenclaturally. The nomenclatural confusion between Elettaria cardamomum (L.) Maton and certain other names in Amomum is discussed, and the identity of A. compactum is clarified with respect to A. verum Blackw. More than one element of original material of A. compactum has been located and a lectotype is chosen. The identity of A. kepulaga Burkill & Sprague is discussed and a lectotype chosen.